Better Students Ask More Questions.
Solve: −3x + 2x = 6
2 Answers | add yours
It is extremely easy to solve for x from the equation you have have.
-3x + 2x = 6
add the left hand terms
=> -x = 6
multiply both the sides by -1
=> x = -6
The solution of the equation is x = -6
Posted by justaguide on September 8, 2011 at 10:27 AM (Answer #1)
add the two x factors together. you get:
Posted by snickel1 on September 9, 2011 at 4:07 AM (Answer #2)
Join to answer this question
Join a community of thousands of dedicated teachers and students.